Sustainability Performance of Village Credit Institutions (LPD) in Buleleng Regency - Novi Budiasni; Sri Ayuni; Wulan Sari Sanjaya (International Journal of Social Science and Business, 2018)
Measurement and Performance appraisal are the important component of the Village Credit Institution (LPD). The management can also use LPD performance measurement as a tool to evaluate its business performance. There is a weakness in performance measurement, namely performance measurement that only measures financial performance, but has not been able to fully describe the condition of LPD to non-financial performance. This research was explanatory with the form of causality between variables. The number of LPD to be sampled were 59 LPD. The data analysis technique used in this study was SEM-PLS. Based on the results of hypothesis testing showed that the performance of the non-financial perspective has a significant positive effect on the performance of the financial perspective of the LPD in Buleleng Regency. Second, the performance of non-financial perspectives has a significant positive effect on the performance of a social perspective based on Tri Hita Karana LPD in Buleleng Regency. The three financial perspective performance and non-financial perspective performance have a significant positive effect on the performance of a social perspective based on Tri Hita Karana LPD in Buleleng Regency.